2008
DOI: 10.1590/s0101-20612008000200023
|View full text |Cite
|
Sign up to set email alerts
|

Interference of heating on the antimicrobial activity and chemical composition of Origanum vulgare L. (Lamiaceae) essential oil

Abstract: ResumoO óleo essencial de Origanum vulgare L. Lamiaceae (orégano) apresenta variadas propriedades biológicas, de modo que seu potencial antimicrobiano tem despertado interesse para uso na conservação de alimentos. Este estudo objetivou avaliar a interferência de diferentes tratamentos térmicos (60, 80, 100 e 120 °C/1 hora) sobre a efetividade antimicrobiana e composição química do óleo essencial de O. vulgare. A efetividade antimicrobiana do óleo essencial exposto aos diferentes tratamentos térmicos foi avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…The estimated number of plant species, only a small percentage had their pharmacological properties studied (34), like this, there is need to search for new drugs from plants that have therapeutic potential. Therefore, the essential oils are important because their several pharmacological activities including anti-fungal, antibacterial, antiparasitic (2,4,37). …”
Section: Discussionmentioning
confidence: 99%
“…The estimated number of plant species, only a small percentage had their pharmacological properties studied (34), like this, there is need to search for new drugs from plants that have therapeutic potential. Therefore, the essential oils are important because their several pharmacological activities including anti-fungal, antibacterial, antiparasitic (2,4,37). …”
Section: Discussionmentioning
confidence: 99%
“…Some essential oils display strong antimicrobial activity, selectivity against Gram-negative over Gram-positive bacteria ( Lin et al, 2000 ). De Souza et al (2008) found no significant interference on the essential oil antimicrobial activity and chemical composition under different heating treatments (room temp. to 120°C).…”
Section: Introductionmentioning
confidence: 85%
“…The results showed that all of the supercritical fluid extraction fractions exhibited antimicrobial effects on tested microorganisms, and the most efficient fraction was obtained with 7% ethanol at 150 bar and 40 °C. De Souza et al [ 36 ] evaluated the effects of heating (at the temperatures of 60, 80, 100, and 120 °C, at a duration of 1 h for each) on the antimicrobial activities of oregano EO against 9 microorganism strains ( C . albicans , Candida krusei ( C .…”
Section: Oreganomentioning
confidence: 99%